Irish hospital finance - Hargadon, O. P. (Statistical and Social Inquiry Society of Ireland, 1956)
It will be readily understood that the energies of the local and central Government bodies in the 1920's were very considerably absorbed by general tasks of national reconstruction, with the result that little could be achieved in the way of provision of new hospitals or the extension of hospital services. Six new district hospitals were, in fact, built, and considerable efforts were made to improve the existing accommodation and equipment of other local authority institutions. In the voluntary hospitals capital development was equally limited. For the purposes of a broad review of financial aspects of the hospitals the 1920's may, therefore, be regarded as a mere continuation of the nineteenth century, and the ?current period? may be regarded as commencing in the early 1930's. The financial administration of any large undertaking falls naturally into two classifications?capital and revenue?and it is proposed to approach the examination of the hospital finances of the current period from these standpoints.
Read before the Society, 20 April 1956
Keywords: Healthcare; Hospital finance in Ireland; Public health expenditure; 314.15